Antidiarrheal Activity of Extract from Herba kummerowiae in Mice - Liu, Haohua; Hu, Xuesong; Xu, Bing; Li, Min; Cui, Zeshi; Zhang, Dongfang (Asian Journal of Chemistry, 2013)
Herba kummerowiae is a traditional Chinese herb with functions of heat-clearing, detoxicating, promoting urination and antidiarrhea and have been used in the treatment of gastroenteritis, dysentery and urinary system infection. There is few research on chemical composition activities, pharmacology, etc. In this study, the extract from Herba kummerowiae was analyzed by HPLC, two kinds of compouds including genistein, kaempferol were identifed. The content was respectively 0.16 and 0.37 %. Through the senna leaf diarrhea model, antidiarrheal activity of the extract in mice was studied. Compared with the model control group, the loose stools rate and diarrhea index were reduced by Herba kummerowiae, xiaoer xiesuting granule and montmorillonite powder (p < 0.05). The effect of inhibitting peristalsis was related with the dose of Herba kummerowiae and the effect was weaker than montmorillonite powder. The results show that Herba kummerowiae is effective in diarrhea and more suitable for children or the aged.